The quality of father-child feeding interactions mediates the effect of maternal depression on children’s psychopathological symptoms - Cimino, Silvia; Tambelli, Renata; Di Vito, Paola; D’Angeli, Gessica; Cerniglia, Luca (Frontiers in Psychiatry, 2022)
Research has shown that Postnatal maternal depression (PND) is associated with children’s emotional and behavioral problems during infancy, but the possible effect of father-child relationship quality on this association is yet to be thoroughly investigated. We recruited 401 families (802 parents; 401 children) via mental health clinics in Central Italy. We divided families into two groups: Group 1 included families with mothers with PND; Group 2 included families with mothers without PND (control group). The assessment took place at T1 (18 months of age of children) and T2 (36 months of age of children): postnatal maternal depression was measured through the Edinburgh Postnatal Depression Scale (EPDS); parent-child relationship quality was assessed through the Scale for the Assessment of Feeding Interactions (SVIA); and the child emotional–behavioral functioning was evaluated with the Child-Behavior-Checklist (CBCL). Compared to the control group, the children of the groups where mothers had PND, showed overall higher scores (i.e. more maladaptive) on the CBCL. A direct effect of postnatal maternal depression on children’s emotional-behavioral functioning was found, both at T1 and at T2. A mediation effect of father-child relationship quality between postnatal maternal depression and child outcomes was also found. These results could inform prevention and intervention programs in families with mothers with PND.